Pengaruh Promosi Kesehatan Perilaku Hidup Bersih dan Sehat (PHBS) pada Tatanan Sekolah terhadap Pengetahuan PHBS Siswa Kelas IV dan V di SD Negeri Ngemplak Surakarta - Ameta, Nur Izah; Soebagyo, Bambang; Sumardiyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Health promotion can improve knowledge, attitudes and behavior, particullary knowledge of Clean and Healthy Behavior. This study aims to prove the effect of health promotion on knowledge of Clean and Healthy Behavior. Methods: This research is a pre-experimental design with the plan of one-group pretest posttest design was held on 12 April 2013 at SD Negeri Ngemplak Surakarta. The study population was all students of SD Negeri Ngemplak Surakarta totaling 230 people. While the sampling carried out by simple random sampling in grade students IV and V. The sample consisted of 32 grade students IV and 38 grade students V. Then the total number of samples is 70 students. The independent variable in this study is a health promotion of clean and healthy behavior in the order of school a measurement tool slides and posters. As for the dependent variable is the knowledge of clean and healthy behavior are measured using a questionnaire that have been tested for validity and reliability. Analyzed using marginal homogeneity test through SPSS 16.0 for Windows program. Results : This research shows a increased knowledge after health promotion Clean and Healthy Behavior a number of 62 students or 88.57% of all students in attendance, knowledge of students decreased a number of 2 students or 2.8% and a fixed 6 students or 8.57 % and the marginal homogeneity test results showed p = 0.000. Conclusion:. There is the influence of health promotion of clean and healthy behavior in the order of school to knowledge clean and healthy behavior students in class IV and V SD Negeri Ngemplak Surakarta. Students who are knowledgeable well after the intervention more than ever before. Keywords: health promotion of PHBS, knowledge PHBS